Urban pertussis epidemiological patterns in a highly vaccinated megacity: Policy impacts and control strategies in Chongqing, China, 2005-2024 - Rui Shen; Jiawei Xu; Yugang Li; Jianxing Yu; Na Sun; Zilu Xu; Xueying Xu; Xiao Liu; Yang Liu; Bosong Li; Li Qi; Luzhao Feng (International Journal of Infectious Diseases)
Objectives: Despite high vaccination coverage, pertussis resurgence in megacities challenges conventional control strategies. We investigated epidemiological patterns and policy impacts in a densely populated urban setting in Chongqing, China. Methods: Using population-based surveillance data (2005-2024) from Chongqing (population 32.1 million; DTP3 coverage >97%), we conducted hierarchical Bayesian spatial modeling and age-structured Susceptible-Infected-Recovered-Vaccinated transmission analysis. We assessed four sequential policy transitions and simulated four vaccination strategies over three years (2025-2027) to evaluate their potential impact. Results: Annual pertussis incidence increased from 0.25 to 70.82/100,000. Infants showed highest absolute risk, while children aged 6-7 years demonstrated elevated risk (RR: 0.55 and 0.54, respectively). Urban areas showed marginally elevated risk (RR: 1.04, 95% CI: 1.00-1.07). Molecular diagnostics implementation revealed substantial hidden transmission (RR: 82.65, 95% CI: 73.47-92.99). Modeling projected extended school-age boosters (ages 5-7 years) would reduce incidence by 47.93%, targeted vaccination of ages 6-7 years achieved 36.64% reduction, and the national benchmark with 6-year booster reduced incidence by 19.09%. All strategies provided substantial indirect protection to infants without direct intervention. Conclusion: Enhanced molecular surveillance uncovered substantial hidden transmission in urban settings. Strategic school-age targeted vaccination could effectively disrupt urban transmission chains while protecting vulnerable infants.